Changes in Physiological Parameters after Combined Exercise according to the I/D Polymorphism of hUCP2 Gene in Middle-Aged Obese Females. - Sang Duk Oh (Tehran University of Medical Sciences, 2014)
The purpose of this study was to determine whether a 45 bp insertion/deletion (I/D) polymorphism in human uncoupling protein 2 (hUCP2) gene was associated with changes in several cardiovascular risk and physical fitness factors in response to combined exercise during 12 weeks in Korean middle-aged women. The changes in physiological parameters after combined exercise during 12 weeks were compared between each genotype subgroups of hUCP2 gene to clarify the inter-individual differences in exercised-induced changes according to genetic predisposition.A total of 185 women aged over 40 years living in Seoul, Korea were participated in this study, and analyzed before and after 12 weeks on combined exercise including aerobic exercise and strength training for body composition, hemodynamic parameters, physical fitness and metabolic variables. A 45 bp I/D polymorphism in hUCP2 gene was genotyped by polymerase chain reaction (PCR) amplification and agarose gel electrophoresis method.Combined exercise program during 12 weeks indicated the significant health-promoting effects for our participants on multiple body composition, hemodynamic parameters, physical fitness factors and metabolic parameters, respectively. With respect to a 45 bp I/D polymorphism in hUCP2 gene, this polymorphism was significantly associated with baseline %body fat of our participants (P